Enhancing Cystic Fibrosis Immune Regulation - van Heeckeren, Anna M.; Sutton, Morgan T.; Fletcher, David R.; Hodges, Craig A.; Caplan, Arnold I.; Bonfield, Tracey L. (Frontiers in Pharmacology, 2021)
Immunity is the host response to pathogen/environmental exposure. In cystic fibrosis (CF), the chronic of infection and inflammation results in debilitating and often fatal disease. Advancement in CF therapeutics has provided successful treatment regiments for a variety of clinical consequences in CF. Still, treating the chronic lung infection and inflammation in CF continues to be problematic. Even with the advent of new small molecule cystic fibrosis transmembrane conductance regulator (CFTR) correctors and potentiators, there is only a modest effect on the established infection and inflammation. Further, anti-inflammatory therapeutics are problematic due to the concurrent infectious status of the patients potentially contributing to exacerbations in pathogen colonization and symptoms. Enhancing CF patient’s own immune repertoire might provide the opportunity to optimize management of infection and inflammation especially in this era of innovative small molecule therapy. The work in this manuscript focuses on testing the hypothesis of whether supplemental or alternative modulating immune support can enhance the capacity to manage infection and inflammation in CF.